2015
DOI: 10.1111/jam.12925
|View full text |Cite
|
Sign up to set email alerts
|

First detection of papillomaviruses and polyomaviruses in swimming pool waters: unrecognized recreational water-related pathogens?

Abstract: To the best of our knowledge, this is the first report on human papillomaviruses and polyomaviruses in swimming pools. The likelihood that these viruses can be transmitted by recreational activities deserves to be explored in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…Hannigan et al (2015) recently supported the previous findings by showing that members of the family Papillomaviridae were most abundant on the palm of healthy individuals. Further support to the previous findings can be found in a study where HPVs were detected in recreational water, such as swimming pool waters (La Rosa et al, 2015). As suggested by the authors, their stability in water environments is not well-understood, and the likelihood of their transmission by recreational activities and potential impact on human or animal health arising from the presence of HPVs genomes deserves to be explored further.…”
Section: Resultssupporting
confidence: 78%
“…Hannigan et al (2015) recently supported the previous findings by showing that members of the family Papillomaviridae were most abundant on the palm of healthy individuals. Further support to the previous findings can be found in a study where HPVs were detected in recreational water, such as swimming pool waters (La Rosa et al, 2015). As suggested by the authors, their stability in water environments is not well-understood, and the likelihood of their transmission by recreational activities and potential impact on human or animal health arising from the presence of HPVs genomes deserves to be explored further.…”
Section: Resultssupporting
confidence: 78%
“…These outcomes in both sewage and stool samples are similar to the findings of the previously reports conducted in Egypt or worldwide, which demonstrated that this virus is highly abundant in sewage as well as stool samples. Moreover, the virus may reach wastewaters as a result of shedding in feces which support its probability to be transmitted via fecal-oral route (Hamza et al, 2018;Iaconelli et al, 2015;La Rosa et al, 2015;Kitajima et al, 2014;Vanchiere et al, 2009;Vanchiere et al, 2005). Indeed, 83.3%, 53.3% and 100% of raw wastewater, treated effluent and activated sludge samples were positive for HPyV, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…In 2013–2014, a study investigated the presence of human enteric viruses (adenovirus, norovirus, and enterovirus) in indoor and outdoor swimming pool waters in Rome. Bacteriological parameters (fecal indicator bacteria, heterotrophic plate count, Pseudomonas aeruginosa , and Staphylococcus aureus ) were also investigated [43]. Moreover, the study was the first to examine the occurrence of non-enteric viruses in swimming pool waters: human papillomavirus (HPV) and human polyomavirus (HPyV).…”
Section: Occurrence Of Enteric Viruses In Swimming Pools Under Nonmentioning
confidence: 99%